Preparation method of Sc-doped YSZ thermal spraying powder and Sc-doped YSZ thermal spraying powder

Through microemulsion system and plasma spheroidization technology, the Sc-doped YSZ thermal spray powder was prepared, which solved the problem of rare earth elements entering the zirconia lattice, realized the preparation of high-performance rare earth-doped YSZ coating, and improved the powder Fluidity and density simplify the process and reduce costs.

CN119191839AInactive Publication Date: 2024-12-27XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411702678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing preparation methods for rare earth doped YSZ thermal spray powder are difficult to ensure that the rare earth elements completely enter the zirconia lattice, resulting in insufficient performance, and the chemical reaction synthesis of nanoparticles is prone to agglomeration, and the size control is difficult, resulting in poor performance.

Method used

The metal salt solution was dissolved by a microemulsion system, and the Sc doped YSZ precursor nanosolution was generated through hydrolysis reaction, and the solution was replaced and dried to form a nanopowder, followed by ball milling and spray drying, and finally, the Sc doped was prepared by plasma spheroidization and densification. Miscellaneous YSZ thermal spray powder.

Benefits of technology

It realizes high-performance preparation of rare earth doped YSZ coating, avoids agglomeration, regulates the particle size of nano powder, improves the fluidity and loose density of thermally sprayed powder, has high processing efficiency and low cost, and is suitable for industrial applications. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191839A_ABST
    Figure CN119191839A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a preparation method of Sc-doped YSZ thermal spraying powder and the Sc-doped YSZ thermal spraying powder, and relates to the technical field of ceramic powder.The method comprises the steps that a surfactant, a cosurfactant, an oil phase and a water phase are matched to obtain a micro-emulsion system, various metal salt solutions are dissolved in the micro-emulsion system, and the Sc-doped YSZ thermal spraying powder is obtained; regulating and controlling the micro-emulsion system through a precipitant to carry out hydrolysis reaction so as to obtain an Sc-doped YSZ precursor nano solution; carrying out solution replacement and drying treatment on the Sc-doped YSZ precursor nano solution so as to generate Sc-doped YSZ precursor nano powder; preparing the Sc-doped YSZ precursor nano powder into slurry, carrying out ball milling, and carrying out spray drying to obtain an Sc-doped YSZ aggregate; and the Sc doped YSZ aggregate is densified through plasma spheroidizing, and the Sc doped YSZ thermal spraying powder is obtained. The performance of the thermal spraying powder can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The disclosed embodiments relate to the technical field of ceramic powders, and in particular to a method for preparing Sc-doped YSZ thermal spray powder and Sc-doped YSZ thermal spray powder. Background Art

[0002] With the continuous development of aviation industry, thermal barrier coatings have been widely used in aviation engines and ground gas turbines to provide thermal protection for hot end metal parts and improve the operating temperature and efficiency of gas turbines. Yttria-stabilized zirconia (YSZ) is currently the most ideal thermal barrier coating material due to its good thermal cycle, high melting point and low thermal conductivity.

[0003] However, as the thrust-to-weight ratio of aircraft engines continues to increase, thermal barrier coatings on the surface of hot end components face more severe problems such as thermal mismatch, high-temperature oxidation, and high-temperature corrosion, which also puts higher demands on their service performance. Therefore, it is urgent to develop new thermal barrier coating materials to achieve long-term stable service at higher temperatures.

[0004] In order to solve the above problems, the life of YSZ coating can be improved by rare earth doping. For the preparation process of rare earth doped YSZ powder, one method is to rely on mixed ball milling of oxide powder and achieve rare earth doping by solid-state diffusion. However, this method is difficult to ensure that the rare earth elements completely enter the zirconia lattice, resulting in insufficient performance of the final thermal spray powder; another method is to synthesize nanoparticles through chemical reactions and then granulate and densify. The nanoparticles prepared by the early chemical reaction are very easy to agglomerate and the size is difficult to control, which will also lead to poor performance of the final thermal spray powder. Summary of the invention

[0005] The purpose of the present disclosure is to provide a preparation method of Sc-doped YSZ thermal spray powder and Sc-doped YSZ thermal spray powder, thereby at least to a certain extent overcoming the problem of poor performance of Sc-doped YSZ thermal spray powder caused by limitations and defects of related technologies.

[0006] According to one aspect of the present disclosure, a method for preparing a Sc-doped YSZ thermal spray powder is provided, comprising: mixing a surfactant, a co-surfactant, an oil phase and an aqueous phase to obtain a microemulsion system, dissolving a plurality of metal salt solutions in the microemulsion system, and regulating the microemulsion system to undergo a hydrolysis reaction by a precipitant to obtain a Sc-doped YSZ precursor nano-solution; subjecting the Sc-doped YSZ precursor nano-solution to solution replacement and drying treatment to generate a Sc-doped YSZ precursor nano-powder; configuring the Sc-doped YSZ precursor nano-powder into a slurry, ball milling the Sc-doped YSZ precursor nano-powder, and spray drying the Sc-doped YSZ agglomerates; and densifying the Sc-doped YSZ agglomerates by plasma spheroidization to obtain a Sc-doped YSZ thermal spray powder.

[0007] In an exemplary embodiment of the present disclosure, the mass ratio of the surfactant: the co-surfactant: the oil phase is (0.1-4): (0.5-2): (5-10).

[0008] In an exemplary embodiment of the present disclosure, the surfactant is any one of an anionic surfactant, a cationic surfactant and a nonionic surfactant.

[0009] In an exemplary embodiment of the present disclosure, the co-surfactant is one or more of n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, and isopentanol, and the oil phase is one or more of cyclohexane, n-hexane, xylene, n-octanol, toluene, and ethanol.

[0010] In an exemplary embodiment of the present disclosure, the multiple metal salt solutions include one or more of Zr(NO3)4·H2O or ZrOCl2·8H2O, Y(NO3)3·H2O or YCl3·6H2O, Sc(NO3)3·H2O or ScCl3·6H2O, the concentration of the metal salt solution is 0.02~0.2mol / L, and the pH value of the metal salt solution is adjusted to 8~11.

[0011] In an exemplary embodiment of the present disclosure, the solution replaced by the solution is one or more of ethanol, methanol, and acetone, the amount of water replaced by the solution is 0-1 L, and the drying temperature is 60-150° C.

[0012] In an exemplary embodiment of the present disclosure, the concentration of the slurry is 10-50 wt %; the inlet air temperature of the spray drying is 150-200° C., the outlet air temperature is 80-120° C., the feed speed is 10-100 r / min, and the centrifugal speed is 100-200 HZ.

[0013] In an exemplary embodiment of the present disclosure, the power of the plasma spheroidization is 50-150 kW, the powder feeding rate is 10-50 g / min, and the protective gas during the plasma spheroidization process is an inert gas.

[0014] In an exemplary embodiment of the present disclosure, the Sc-doped YSZ thermal spray powder has a bulk density of 1.6-2.2 g / cc and a fluidity of less than 50s / 50g.

[0015] According to one aspect of the present disclosure, a Sc-doped YSZ thermal spray powder is provided. The Sc-doped YSZ thermal spray powder is prepared according to any one of the above methods for preparing the Sc-doped YSZ thermal spray powder.

[0016] In the technical solution provided in the embodiments of the present disclosure, on the one hand, Sc-doped YSZ nanopowder is prepared by a microemulsion system to ensure that the doping elements are completely introduced into the zirconia lattice, thereby realizing the preparation of high-performance rare earth-doped YSZ coatings; in addition, a layer of emulsifier molecules is coated on the surface to prevent the particles from agglomerating, and the reaction is carried out in the water core, which can effectively regulate the particle size of the nanopowder and provide favorable guarantees for the preparation of Sc-doped YSZ thermal spray powder; and the processing efficiency is high, the operation is simple, the cost is low, and it is easy to apply industrially. On the other hand, densification through plasma spheroidization can improve the porosity of the thermal spray powder, thereby improving the fluidity and bulk density performance of the thermal spray powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0018] Figure 1 A flow chart schematically shows a method for preparing Sc-doped YSZ thermal spray powder in an embodiment of the present disclosure.

[0019] Figure 2 A schematic diagram of a scanning microscopic image of thermal spray powder prepared by a solid phase method is shown schematically.

[0020] Figure 3 Schematic diagram of a scanning microscopic image of the thermal spray powder prepared according to Example 1 in the embodiments of the present disclosure.

[0021] Figure 4 Schematic diagram of a scanning microscopic image of a precursor nanopowder prepared according to Example 2 in the embodiments of the present disclosure.

[0022] Figure 5 Schematic diagram of XRD of the thermal spray powder prepared according to Example 2 in the embodiments of the present disclosure.

[0023] Figure 6 Schematic diagram of a scanning microscopic image of the thermal spray powder prepared according to Example 2 in the disclosed embodiment.

[0024] Figure 7 Schematic diagram of a scanning microscopic image of the thermal spray powder prepared according to Example 3 in the disclosed embodiment. DETAILED DESCRIPTION

[0025] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0026] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0027] In order to solve the above technical problems, the present disclosure provides a method for preparing Sc-doped YSZ thermal spray powder, which is used to prepare Sc-doped YSZ powder for thermal spraying. Figure 1 As shown in , it mainly includes the following steps: In step S110, a surfactant, a co-surfactant, an oil phase and an aqueous phase are mixed to obtain a microemulsion system, a plurality of metal salt solutions are dissolved in the microemulsion system, and the microemulsion system is regulated by a precipitant to undergo a hydrolysis reaction to obtain a Sc-doped YSZ precursor nano-solution; In step S120, the Sc-doped YSZ precursor nano-solution is subjected to solution replacement and drying treatment to generate Sc-doped YSZ precursor nano-powder; In step S130, the Sc-doped YSZ precursor nanopowder is prepared into a slurry, ball-milled, and spray-dried to obtain Sc-doped YSZ agglomerates; In step S140, the Sc-doped YSZ agglomerates are densified by plasma spheroidization to obtain Sc-doped YSZ thermal spray powder.

[0028] Next, the preparation method of the Sc-doped YSZ thermal spray powder in the embodiment of the present disclosure is specifically described.

[0029] In step S110, a surfactant, a co-surfactant, an oil phase and an aqueous phase are mixed to obtain a microemulsion system, a plurality of metal salts are dissolved in the microemulsion system, and the microemulsion system is regulated by a precipitant to undergo a hydrolysis reaction to obtain a Sc-doped YSZ precursor nano-solution.

[0030] In the disclosed embodiments, the surfactant may be an anionic surfactant, a cationic surfactant or a nonionic surfactant. Among them, the anionic surfactant may be, for example, AOT (sodium bis(ethylhexyl) succinic acid sulfonate), SDB (sodium dodecylbenzene sulfonate), SDS (sodium dodecyl sulfate). The cationic surfactant may be, for example, CTAC (hexadecyl trimethyl ammonium chloride), DTAB (dodecyl trimethyl ammonium bromide), CTAB (hexadecyl trimethyl ammonium bromide). The nonionic surfactant may be, for example, Triton-100 (nonylphenol polyoxyethylene ether), Npn (nonylbenzene polyoxyethylene ether surfactant), Tween-40 (60, 80), Span-40 (60, 80), etc. The co-surfactant may be a medium-chain alcohol, and the medium-chain alcohol may be, for example, one or more of n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, and isopentanol. The oil phase may be one or more of cyclohexane, n-hexane, xylene, n-octanol, toluene, and ethanol. The aqueous phase may be deionized water.

[0031] In some embodiments, the mass ratio of surfactant, co-surfactant and oil phase can be expressed as: mass ratio of surfactant:co-surfactant:oil phase=(0.1~4):(0.5~2):(5~10).

[0032] Among them, the multiple metal salt solutions may include one or more of Zr(NO3)4·H2O or ZrOCl2·8H2O, Y(NO3)3·H2O or YCl3·6H2O, Sc(NO3)3·H2O or ScCl3·6H2O. The mass of the multiple metal salt solutions can be obtained according to the configuration of different weight ratios of Sc2O3:Y2O3:ZrO2. The concentration of the metal salt solution can be 0.02~0.2 mol / L. Further, the multiple metal salt solutions can be added to the microemulsion system for dissolution, and the microemulsion system is regulated by a precipitant to perform a hydrolysis reaction to obtain a Sc-doped YSZ precursor nano solution. The precipitant can be one or more of a urea solution, an ammonium bicarbonate solution, and an ammonium hydroxide solution. After adding the precipitant, the pH value of the metal salt solution can be adjusted to 8~11.

[0033] In step S120 , the Sc-doped YSZ precursor nano-solution is subjected to solution replacement and drying treatment to obtain Sc-doped YSZ precursor nano-powder.

[0034] In the disclosed embodiment, the Sc-doped YSZ precursor nano-solution obtained in step S110 can be cleaned by centrifugation to remove chloride ions in the Sc-doped YSZ precursor nano-solution, and then the solution is replaced. The solution used to achieve the solution replacement can be one or more of ethanol, methanol, and acetone. The amount of replacement water for the solution replacement can be 0~1L. After the solution replacement, a drying treatment can be performed to obtain a Sc-doped YSZ precursor nano-powder, and the drying temperature of the drying treatment is 60~150°C.

[0035] Next, in step S130 , the Sc-doped YSZ precursor nanopowder is configured into a slurry, ball-milled, and spray-dried to obtain Sc-doped YSZ agglomerates.

[0036] In the disclosed embodiment, Sc-doped YSZ precursor nanopowder is mixed with water to form a slurry and ball-milled, and the concentration of the slurry can be 10-50 wt%. The ball-milling time can be set according to actual needs. The process conditions of spray drying can be: inlet air temperature 150-200°C, outlet air temperature 80-120°C, feed speed 10-100 r / min, centrifugal speed 100-200HZ. After spray drying, Sc-doped YSZ agglomerates can be obtained.

[0037] In step S140, the Sc-doped YSZ agglomerates are densified by plasma spheroidization to obtain Sc-doped YSZ thermal spray powder.

[0038] In the disclosed embodiment, the Sc-doped YSZ agglomerates can be densified by plasma spheroidization. The process conditions of plasma spheroidization include: the power of plasma spheroidization is 50-150 kW, the powder feeding rate is 10-50 g / min, and the protective gas during the plasma spheroidization process is an inert gas, such as nitrogen, argon, etc.

[0039] After plasma spheroidization of Sc-doped YSZ agglomerates, Sc-doped YSZ thermal spray powders can be obtained. The size of the Sc-doped YSZ thermal spray powders is 15-45 um, the bulk density of the Sc-doped YSZ thermal spray powders is 1.6-2.2 g / cc, and the fluidity is less than 50s / 50g.

[0040] On this basis, the preparation method of the Sc-doped YSZ thermal spray powder disclosed in the present invention can be specifically described in combination with the embodiments.

[0041] In some embodiments, 7.5Sc2.7YSZ thermal spray powder can be prepared by a solid phase method, comprising the following steps: Step 1: Weigh 7.5 wt% Sc2O3:2.7 wt% Y2O3:89.8 wt% ZrO2 raw materials.

[0042] Step 2: Prepare the slurry at 45-55% solid content using a stirred ball mill, and use 0.1% PVA as a binder to obtain a uniformly dispersed slurry; in addition, in order to avoid the residue of larger agglomerates, the slurry is sieved through a 20-mesh standard sieve.

[0043] Step 3: Use a high-speed centrifugal spray drying system to perform spray drying and granulation treatment at a centrifugal speed of 100 Hz, with an inlet temperature of 150° C. and an outlet temperature of 120° C. to obtain Sc-doped YSZ agglomerates.

[0044] Step 4: The Sc-doped YSZ agglomerates were heat treated at 1400°C for 30 min with a heating rate of 5 min, and then cooled in the furnace to obtain a densified powder.

[0045] Figure 2 The scanning micrograph of 7.5Sc2.7YSZ thermal spray powder is shown in FIG. Figure 2 It can be concluded that the thermal spray powder obtained by the solid phase method has poor sphericity and uneven size. Its fluidity is 90s / 50g and its bulk density is 1.0 g / cc.

[0046] In order to solve the technical problems existing in the process of preparing 7.5Sc2.7YSZ thermal spray powder by solid phase method, a method for preparing Sc-doped YSZ thermal spray powder is provided in an embodiment of the present disclosure. The method is mainly used to prepare Sc-doped YSZ powder that can be thermally sprayed.

[0047] The preparation method of the Sc-doped YSZ thermal spray powder is described in detail below with reference to the examples.

[0048] It should be noted that in the process of preparing Sc-doped YSZ thermal spray powder, one or more parameters including the type of metal salt solution, the mass ratio of the metal salt solution, the ratio of the surfactant, the co-surfactant and the oil phase, the concentration of the metal salt solution, the added precipitant, and the pH value of the Sc-doped YSZ precursor nano solution can be adjusted. In addition, the process conditions of the spray drying and plasma spheroidization processes can also be adjusted.

[0049] Example 1 The material composition is 8.1wt%Sc2O3:3.4wt%Y2O3:88.5wt%ZrO2, abbreviated as 8.1Sc3.4YSZ. The preparation method of thermal spraying Sc-doped YSZ powder mainly includes the following steps: Step 1: Calculate the mass of Sc(NO3)3·H2O, Y(NO3)3·H2O, and Zr(NO3)4·H2O according to the weight ratio of Sc2O3:Y2O3:ZrO2 of 8.1:3.4:88.5 to prepare the metal salt solution. Add the metal salt solution into a 200 mL microemulsion system, in which the mass ratio of surfactant:cosurfactant:oil phase is 0.1:2:5. The concentration of the metal salt solution is 0.1 mol / L. Add urea solution dropwise to the 200 mL microemulsion system under stirring, and adjust the pH value of the metal salt solution to 8.

[0050] Step 2: The Sc-doped YSZ precursor nano-solution obtained in step 1 is washed by centrifugation to remove chloride ions in the solution, and then the solution is replaced with 1 L of methanol, and dried at 60° C. to obtain Sc-doped YSZ precursor nano-powder.

[0051] Step 3: The Sc-doped YSZ precursor nanopowder obtained in step 2 was mixed with water to form a slurry with a concentration of 10wt%. After ball milling, the Sc-doped YSZ agglomerates were obtained by spray drying under the process conditions of an inlet air temperature of 150°C, an outlet air temperature of 120°C, a feed speed of 10 r / min, and a centrifugal speed of 100 Hz.

[0052] Step 4: The Sc-doped YSZ agglomerates of step 3 were plasma spheroidized under the process conditions of power of 50 kW, powder feeding rate of 10 g / min, and protective gas of nitrogen to obtain 8.1Sc3.4YSZ thermal spray powder with a size of 15-45 um. The flowability of the thermal spray powder was 45s / 50g and the bulk density was 2.0 g / cc.

[0053] Figure 3 The scanning microscopic image of the 8.1Sc3.4YSZ thermal spray powder prepared according to Example 1 is schematically shown in FIG. Figure 3 It can be concluded that the thermal spraying powder prepared in Example 1 has good sphericity and size uniformity.

[0054] Example 2 The material composition is 7.5 wt% Sc2O3:2.7 wt% Y2O3:89.8 wt% ZrO2, abbreviated as 7.5Sc2.7YSZ. The preparation method of thermal spraying Sc-doped YSZ powder includes the following steps: Step 1: Calculate the mass of Sc(NO3)3·H2O, Y(NO3)3·H2O, and Zr(NO3)4·H2O according to the weight ratio of Sc2O3:Y2O3:ZrO2 of 7.5:2.7:89.8 to obtain various metal salt solutions. Add various metal salt solutions into a microemulsion system containing 300 mL, wherein the mass ratio of surfactant:cosurfactant:oil phase in the microemulsion system is 1:1.3:7, and the concentration of the metal salt solution is 0.2 mol / L. Add ammonium bicarbonate solution dropwise into the 300 mL microemulsion system under stirring, and adjust the pH value of the metal salt solution to 11.

[0055] Step 2: The Sc-doped YSZ precursor nano-solution obtained in step 1 is washed by centrifugation to remove chloride ions in the Sc-doped YSZ precursor nano-solution, and then the solution is replaced with 0.5 L of ethanol, and dried at 100° C. to obtain Sc-doped YSZ precursor nano-powder.

[0056] Step 3: The Sc-doped YSZ precursor nanopowder obtained in step 2 is mixed with water to form a slurry with a concentration of 30 wt% and ball-milled, and then spray-dried under the process conditions of inlet air temperature of 180°C, outlet air temperature of 100°C, feed speed of 30 r / min, and centrifugal speed of 150HZ to obtain Sc-doped YSZ agglomerates.

[0057] Step 4: The Sc-doped YSZ agglomerates of step 3 were plasma spheroidized under the process conditions of power of 100 kW, powder feeding rate of 20 g / min, and protective gas of nitrogen to obtain 7.5Sc2.7YSZ thermal spray powder with a size of 15-45 um.

[0058] Figure 4 FIG. 2 schematically shows a scanning microscopic image of the Sc-doped YSZ precursor nanopowder prepared according to Example 2. Figure 4It can be seen that the 7.5Sc2.7YSZ nanopowder prepared according to Example 2 has good dispersibility and size uniformity.

[0059] refer to Figure 5 The XRD spectrum of the 7.5Sc2.7YSZ thermal spray powder shown in the figure shows that it is a single tetragonal phase of ZrO2 that exists stably and has good crystallinity.

[0060] Figure 6 The scanning microscopic image of the 7.5Sc2.7YSZ thermal spray powder prepared according to Example 2 is schematically shown in FIG. Figure 6 It can be seen that the 7.5Sc2.7YSZ thermal spray powder has good sphericity and high size uniformity. The flowability of the thermal spray powder is 40s / 50g and the bulk density is 2.2 g / cc.

[0061] Example 3 The material composition is 6.3wt%Sc2O3:5.2wt%Y2O3:88.6wt%ZrO2, abbreviated as 6.3Sc5.2YSZ. The preparation method of thermal spraying Sc-doped YSZ powder includes the following steps: Step 1: Calculate the mass of ScCl3·6H2O, Y(NO3)3·H2O, and ZrOCl2·8H2O according to the weight ratio of Sc2O3:Y2O3:ZrO2 of 6.3:5.2:88.6 to obtain various metal salt solutions. Add various metal salt solutions into a microemulsion system containing 400 mL, wherein the mass ratio of surfactant:cosurfactant:oil phase in the microemulsion system is 2:2:10, and the concentration of the metal salt solution is 0.02 mol / L. Add ammonium bicarbonate solution dropwise to the 400 mL microemulsion system under stirring to adjust the pH value of the metal salt solution to 10.

[0062] Step 2: The Sc-doped YSZ precursor nano-solution obtained in step 1 is washed by centrifugation to remove chloride ions in the solution, and then the solution is replaced with 0.1 L of ethanol, and dried at 150° C. to obtain Sc-doped YSZ precursor nano-powder.

[0063] Step 3: The Sc-doped YSZ precursor nanopowder obtained in step 2 is mixed with water to form a slurry with a concentration of 50 wt% and ball-milled, and then spray-dried under the process conditions of inlet air temperature 180°C, outlet air temperature 120°C, feed speed 80r / min, and centrifugal speed 200HZ to obtain Sc-doped YSZ agglomerates.

[0064] Step 4: The Sc-doped YSZ agglomerates obtained in step 3 were plasma spheroidized under the process conditions of power of 150 kW, powder feeding rate of 50 g / min, and protective gas of nitrogen to obtain 6.3Sc5.2YSZ thermal spray powder with a size of 15~45 um.

[0065] Figure 7 The scanning microscopic image of the 6.3Sc5.2YSZ thermal spray powder prepared according to Example 3 is schematically shown in FIG. Figure 7 It can be seen that the 6.3Sc5.2YSZ thermal spray powder has good sphericity and size uniformity. The flowability of the thermal spray powder is 49s / 50g, and the bulk density is 1.8 g / cc.

[0066] In summary, in the embodiments disclosed herein, Sc-doped YSZ nanopowders are prepared by a microemulsion system to ensure that the doping elements completely enter the zirconia lattice, thereby realizing the preparation of high-performance rare earth-doped YSZ coatings; in addition, a layer of emulsifier molecules is coated on the surface to prevent particles from agglomerating, and the reaction is carried out in the water core, which can effectively regulate the particle size of the nanopowders, providing favorable guarantees for the later Sc-doped YSZ thermal spray powders. The processing efficiency is high, the operation is simple, the cost is low, and it is easy to apply industrially. Densification through plasma spheroidization can improve the porosity of the thermal spray powder, thereby improving the fluidity and bulk density performance of the thermal spray powder.

[0067] In the embodiment of the present disclosure, a Sc-doped YSZ thermal spray powder is also provided. The Sc-doped YSZ thermal spray powder can be prepared according to the method of step S110 to step S140.

[0068] In the disclosed embodiment, a Sc-doped YSZ nanopowder with high dispersibility and adjustable particle size is prepared by a microemulsion method, and densification is performed in combination with a plasma device to improve the fluidity and bulk density of the thermal spray powder. The method has high processing efficiency, simple operation, low cost, and is easy to industrialize and apply.

[0069] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0070] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0071] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A method for preparing Sc-doped YSZ thermal spray powder, characterized in that: include: A surfactant, a co-surfactant, an oil phase and an aqueous phase are mixed to obtain a microemulsion system, a plurality of metal salt solutions are dissolved in the microemulsion system, and a precipitant is used to control the microemulsion system to undergo a hydrolysis reaction to obtain a Sc-doped YSZ precursor nano-solution; The Sc-doped YSZ precursor nano-solution is subjected to solution replacement and drying treatment to generate Sc-doped YSZ precursor nano-powder; The Sc-doped YSZ precursor nanopowder is configured into a slurry, ball-milled, and spray-dried to obtain Sc-doped YSZ agglomerates; The Sc-doped YSZ agglomerates are densified by plasma spheroidization to obtain Sc-doped YSZ thermal spraying powder.

2. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The mass ratio of the surfactant:cosurfactant:oil phase is (0.1~4):(0.5~2):(5~10).

3. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The surfactant is any one of anionic surfactant, cationic surfactant and nonionic surfactant.

4. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The co-surfactant is one or more of n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, and isopentanol; the oil phase is one or more of cyclohexane, n-hexane, xylene, n-octanol, toluene, and ethanol.

5. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The multiple metal salt solutions include one or more of Zr(NO3)4·H2O or ZrOCl2·8H2O, Y(NO3)3·H2O or YCl3·6H2O, Sc(NO3)3·H2O or ScCl3·6H2O, the concentration of the metal salt solution is 0.02~0.2mol / L, and the pH value of the metal salt solution is adjusted to 8~11.

6. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The solution replaced by the solution is one or more of ethanol, methanol, and acetone, the amount of water replaced by the solution is 0-1 L, and the drying temperature is 60-150° C.

7. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The concentration of the slurry is 10-50 wt %; the inlet air temperature of the spray drying is 150-200° C., the outlet air temperature is 80-120° C., the feed speed is 10-100 r / min, and the centrifugal speed is 100-200 HZ.

8. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The power of the plasma spheroidization is 50-150 kW, the powder feeding rate is 10-50 g / min, and the protective gas during the plasma spheroidization process is an inert gas.

9. The method for preparing Sc-doped YSZ thermal spray powder according to claim 1, characterized in that: The Sc-doped YSZ thermal spray powder has a bulk density of 1.6-2.2 g / cc and a fluidity of less than 50s / 50g.

10. A Sc-doped YSZ thermal spray powder, characterized in that: The Sc-doped YSZ thermal spray powder is prepared according to the method for preparing Sc-doped YSZ thermal spray powder according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of CMAS-corrosion-resistant double-phase-structure scandium-yttrium rare earth doped zirconium oxide powder

    CN113956037A

  • Yttrium-stabilized zirconia powder and preparation method thereof

    CN117447200A

  • Nano agglomerated rare earth doped YSZ powder and preparation method thereof

    CN118993728A

  • Nano structure yttrium stabilized zirconium oxide aggregated powder and its producing method

    CN1587062A

  • Manufacturing method with particle size control

    WO2020102140A1